An ACF<0.03 low-power software PUF based on the RISC-V processor for IoT security. (March 2022) - Ni, Li; Wang, Pengjun; Zhang, Yuejun; Chen, Jia; Zhang, Huihong; Zhuang, Youyi
Abstract: With the development of the Internet of Things (IoT) technology, more and more occasions require security protection under extreme resource-constrained conditions. The traditional PUF is difficult to function effectively and requires replacement of equipment, which leads to increased product design and time costs. To tackle these problems, we propose a Software Physical Unclonable Functions (SPUF) scheme based on the high robustness of the RISC-V processor. The main contribution is to utilize the low-voltage feature so that the RISC-V processor operates in an unusual state for generating abnormal information, and to use this information to characterize the chip characteristics. Meanwhile, the frequency compensation method is proposed to further optimize the robustness of the SPUF response, and a lightweight SPUF-based authentication protocol is adopted to improve the authentication security. In this way, the safety and reliability of the proposed PUF are evaluated. The experimental results show that the SPUF data passed the National Institute of Standards and Technology (NIST) randomness tests, with an autocorrelation less than 0.03 at 95% confidence level. The averaged Hamming weight and Hamming distance are 0.495 and 0.501, respectively, making it widely applicable to IoT security.